Springer Handbook of Atomic, Molecular, and Optical Physics - Drake, Gordon W. F. (Springer Handbooks,, 2006)
This Springer Handbook of Atomic, Molecular, and Optical Physics comprises a comprehensive reference source that unifies the entire fields of atomic, molecular, and optical (AMO) physics, assembling the principal ideas, techniques and results of the field from atomic spectroscopy to applications in comets. Its 92 chapters are written by over 100 authors, all leaders in their respective disciplines. Carefully edited to ensure uniform coverage and style, with extensive cross references, and acting as a guide to the primary research literature, it is both a source of information and an inspiration for graduate students and other researchers new to the field. Relevant diagrams, graphs, and tables of data are provided throughout the text. Substantially updated and expanded since the 1996 edition and published in conjunction with the 2005 World Year of Physics (commemorating Einstein's 1905 "miracle year"), it contains several entirely new chapters covering current areas of great research interest, such as Bose - Einstein condensation, quantum information, and cosmological variations of the fundamental constants. A fully searchable CD-ROM version of the contents accompanies the handbook. Key Topics Physical Units and Constants Mathematical Methods Atoms Molecules Scattering Theory and Experiment Quantum Optics Applications Features Covers basic theory, methods, and techniques Contains most frequently used formulae and relationships Incorporates the latest CODATA values for fundamental physical constants Contains 288 two-color illustrations and over 100 comprehensive tables Up-to-date approved references Parts and chapters with summaries, detailed index and fully searchable CD-ROM guarantee quick access to data and links to other sources.